(untitled) (Journal of Pharmaceutical Negative Results, 2023)
COVID19 has emerged out as a most pandemic global threatening disease. Current research finding has brought into consideration about the repositioning of ivermectin, an anti-parasitic drug for the treatment of SARS-CoV-2 infected patients. This information augments the knowledge of present and past findings of ivermectin in antiviral research field.